Peer Regulation in a Peer-to-Peer Business Model. (June 2023) - Miao, Li; Lin, Meizhen; Wei, Wei; Moon, Hyoungeun
Peer-to-peer (P2P) businesses in the hospitality and tourism industry pose a regulatory challenge that has disrupted traditional regulatory schemes. This article proposes peer regulation as a form of regulation that complements and supplements command-and-control regulation and platform self-regulation in a P2P business model. Using the polycentric coregulation framework and impression management theory as a theoretical basis, this study systematically explores peer regulation at intrapeer (i.e., self-monitoring and prosocial behaviors), interpeer (i.e., trust-enforcing mechanism and belongingness-enhancing mechanism), and platform (i.e., peer-centric platform self-regulation and de-individualization) levels. The article also discusses critical peer regulation issues such as P2P evaluation and reputation systems in a multifarious regulatory environment, P2P employment, and leveraging platform self-regulation and jurisdictional regulation. This article offers a theoretical account of multilevel peer regulation as a form of P2P regulation and provides future research directions on the topic.